Blood‐Compatible Materials: Vascular Endothelium‐Mimetic Surfaces that Mitigate Multiple Cell‐Material Interactions. Issue 7 (14th January 2021) - Vlcek, Jessica R.; Hedayati, Mohammadhasan; Melvin, Alyssa C.; Reynolds, Melissa M.; Kipper, Matt J.
Abstract: When flowing whole blood contacts medical device surfaces, the most common blood–material interactions result in coagulation, inflammation, and infection. Many new blood‐contacting biomaterials have been proposed based on strategies that address just one of these common modes of failure. This study proposes to mitigate unfavorable biological reactions that occur with blood‐contacting medical devices by designing multifunctional surfaces, with features optimized to meet multiple performance criteria. These multifunctional surfaces incorporate the release of the small molecule hormone nitric oxide (NO) with surface chemistry and nanotopography that mimic features of the vascular endothelial glycocalyx. These multifunctional surfaces have features that interact with coagulation components, inflammatory cells, and bacterial cells. While a single surface feature alone may not be sufficient to achieve multiple functions, the release of NO from the surfaces along with their modification to mimic the endothelial glycocalyx synergistically improves platelet‐, leukocyte‐, and bacteria‐surface interactions. This work demonstrates that new blood‐compatible materials should be designed with multiple features, to better address the multiple modes of failure of blood‐contacting medical devices. Abstract : Surfaces that mimic important features of the endothelial glycocalyx can be optimized to improve cell‐material interactions related to blood‐compatibility. Glycosaminoglycans containing nitric oxide donor groups and organized into biomimetic nanostructures improve platelet, leukocyte, and bacterial responses to surfaces.